ANALISIS PENGUATAN KETAHANAN DAN KEAMANAN TERHADAP CIVITAS AKADEMIKA DI LINGKUNGAN UPN VETERAN JAKARTA - Toby Samuel Tampubolon; Irwan Triadi; Ni Ketut Rania Paramita Swastika; Reyva Cahyaningrum; Satino Satino; Ahmad Khoiril Anam; Ni Nyoman Sudiani; Irawan Irawan; Ronald Manalu (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
The importance of students in efforts to strengthen national resilience cannot be ignored, and strengthening student character and morality is an important aspect in society. Improving students' skills and knowledge in the fields of security and politics is the basis for effective participation in the democratic process and maintaining national security stability. The aim of writing this article is to find out and understand the effectiveness of the security equipment and personnel owned by the campus in maintaining security and resilience in the academic community. The research methods that will be used in this research are quantitative and qualitative methods. The campus has regulations that are effective in maintaining resilience and security in the campus environment, such as the Technical Guidelines for Order, Security and Environmental Safety at the Jakarta Veteran National Development University Campus. Security and order regulations in the campus environment aim to maintain order, security and safety in the campus environment, as well as protecting the rights and obligations of students and other campus residents.